Novel mechanism-based therapeutics for androgen axis blockade in castration-resistant prostate cancer - Teply, Benjamin A. (Curr Opin Endocrinol Diabetes Obes, 2016)
PURPOSE OF REVIEW: Understanding the mechanisms by which castration-resistant prostate cancer progresses provides an opportunity to identify novel therapeutic strategies to treat this disease. This understanding has led to approaches to attack prostate cancer’s androgen axis in unique ways. This review will examine the classes of novel therapies for androgen axis blockade in castration-resistant prostate cancer, with a particular focus on the unique characteristics of drugs in various stages of clinical development. RECENT FINDINGS: The success of abiraterone and enzalutamide has stimulated multiple investigations into novel approaches to attack the androgen-signaling pathway. Drugs under development include cytochrome P17 inhibitors with 17,20-lyase specificity, androgen receptor antagonists that are active against mutated and constitutively-active splice variant forms of the protein, androgen receptor degraders, and bromodomain/BET inhibitors that prevent chromatin binding of activated receptors. The clinical development of several of these experimental agents is reviewed. SUMMARY: Given the unique mechanisms of action for drugs in development, and the possibility that the novel agents may be active in the setting of common resistance mechanisms, treatment options for patients are likely to expand greatly in the coming years. Future studies should prioritize combinations of agents with unique mechanisms of action to optimize outcomes for patients, and should rely on precision-medicine approaches to target known molecular alteration.